2022
DOI: 10.1111/irv.13091
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the upcoming 2022/23 influenza season: A modelling study of the susceptible population in Australia, France, Germany, Italy, Spain and the United Kingdom

Abstract: We analysed the influenza epidemic that occurred in Australia during the 2022 winter using an age-structured dynamic transmission model, which accounts for past epidemics to estimate the population susceptibility to an influenza infection. We applied the same model to five European countries. Our analysis suggests Europe might experience an early and moderately large influenza epidemic. Also, differences may arise between countries, with Germany and Spain experiencing larger epidemics, than France, Italy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In particular, a modeling study using surveillance data from 11 countries in 2017–2022 found a 10–60% increase in the population susceptibility which might lead to a maximum of one-fold to four-fold rise in the epidemic size for the flu season 2022–2023 [ 61 ]. Moreover, early data from the 2022 influenza season in Australia showed that a larger than usual influenza outbreak should be expected in Europe [ 62 ]. These findings highlight the importance of achieving a high influenza vaccination coverage rate across countries.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a modeling study using surveillance data from 11 countries in 2017–2022 found a 10–60% increase in the population susceptibility which might lead to a maximum of one-fold to four-fold rise in the epidemic size for the flu season 2022–2023 [ 61 ]. Moreover, early data from the 2022 influenza season in Australia showed that a larger than usual influenza outbreak should be expected in Europe [ 62 ]. These findings highlight the importance of achieving a high influenza vaccination coverage rate across countries.…”
Section: Discussionmentioning
confidence: 99%
“…Incidents of influenza resurged during the 2021/22 season in many countries in the northern hemisphere 23,43 . However, Japan experienced a 1‐year delay in the resurgence of influenza during the 2022/23 season.…”
Section: Discussionmentioning
confidence: 99%